Nuovi suoni di balenottera comune (Balaenoptera physalus) nel Mediterraneo occidentale - Tranchino, Mirella
Fin whale (Balaenoptera physalus) is the only misticeto commonly observed in the Mediterranean. The males emit sounds, classic pulse products in sequences called songs, at 20Hz for sexual purposes: sounds are produced during the spring for migration to the Tirreno-Ligurian-Provençal basin, the summer feeding area, and during the autumn, when there is a migration to the south to meet the winter breeding season. This area in the Mediterranean sea is unknown. The east coast of the Iberian Peninsula is a migration area. The study was conducted by analyzing through Adobe Audition 3.0 and XBAT softwares files audio of 30 minutes recorded in 2006, in 2011 and 2012 at the level of the Columbretes Islands, in the western Mediterranean sea, using two hearing aids: the MARU, used in 2006 and the EAR, used in 2011 and 2012. From the analysis have emerged that, in addition to songs with pulses of 20 Hz, there are new sounds of fin whale never previously recognized: the VFPs (Variable Frequency Pulses), higher-frequency pulses emitted, between 50 and 120Hz and the ramps, a set of 7-8 pulses, pertaining to a particular song, of increasing frequency. Further studies are needed to understand the importance of these new sounds.